ANALISIS FINACIAL DISTRESS DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yuaniko Paramitra (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
This research was conducted to find out the average value of financial ratios used as a Z-score analysis, to predict bankruptcy, and to find out the development trend (tendency) of the Z-score value in retail companies listed on the Indonesia Stock Exchange. The research method used in this study is a quantitative analysis method. The research object is a retail company listed on the Indonesia Stock Exchange which was selected through the purposive sampling stage or according to the criteria, and has audited financial statements available as secondary data. The result is that there are three retail companies on the Indonesia Stock Exchange which are predicted to experience bankruptcy based on the distress zone condition or the condition of financial difficulties within the company, namely; PT Global Teleshop Tbk with a period of four years (2016-2019), PT Matahari Putra Prima Tbk with a period of three years (2017-2019), PT Trikomsel Oke Tbk with a period of five years (2015-2019).